Increased Risk of Clinically Significant Gallstones following an Appendectomy: A Five-Year Follow-Up Study - Chung, Shiu-Dong (PLoS One, 2016)
Although the vermiform appendix is commonly considered a vestigial organ, adverse health consequences after an appendectomy have garnered increasing attention. In this study, we investigated the risks of gallstone occurrence during a 5-year follow-up period after an appendectomy, using a population-based dataset. We used data from the Taiwan Longitudinal Health Insurance Database 2005. The exposed cohort included 4916 patients who underwent an appendectomy. The unexposed cohort was retrieved by randomly selecting 4916 patients matched with the exposed cohort in terms of sex, age, and year. We individually tracked each patient for a 5-year period to identify those who received a diagnosis of gallstones during the follow-up period. Cox proportional hazard regressions were performed for the analysis. During the 5-year follow-up period, the incidence rate per 1000 person-years was 4.71 for patients who had undergone an appendectomy, compared to a rate of 2.59 for patients in the unexposed cohort (p<0.001). Patients who had undergone an appendectomy were independently associated with a 1.79 (95% CI = 1.29~2.48)-fold increased risk of being diagnosed with gallstones during the 5-year follow-up period. We found that among female patients, the adjusted hazard ratio of gallstones was 2.25 (95% CI = 1.41~3.59) for patients who underwent an appendectomy compared to unexposed patients. However, for male patients, we failed to observe an increased hazard for gallstones among patients who underwent an appendectomy compared to unexposed patients. We found an increased risk of a subsequent gallstone diagnosis within 5 years after an appendectomy.